Leadership Style in Improving the Quality of Education at SMP Birrul Walidain Muhammadiyah Plupuh - Mursyada, Ria Khasna; Pertiwi, Nurkholimah Nanda Dewi; Nandicha, Nabilla Alya; Praditya, Muhamad Irfan; Rozaq, Abdul; Cahyono, Guntur (Edumaspul: Jurnal Pendidikan, 2024)
Education is a deliberate process aimed at developing the potential of students. The principal's significant role in educational institutions ensures the achievement of quality education. The purpose of this research is to explore various leadership styles and strategies implemented by the principal to improve the quality of education at SMP Birrul Walidain Muhammadiyah Plupuh, Sragen Regency, Central Java. Field research methods were used to collect data through interviews, observations, and documentation, with a qualitative descriptive approach. The results found that inclusive, democratic leadership with a family-oriented approach successfully created a conducive school environment for growth and innovation. An effective principal can integrate the educational vision with daily practices at the school, foster strong collaboration between staff and students, and build an environment that supports innovation and continuous learning.